Genetic Polymorphisms: A Novel Perspective on Acute Pancreatitis - Yong Chen; Chao Lian Xie; Ran Hu; Cheng Yi Shen; Mei Zeng; Chang Qiang Wu; Tian Wu Chen; Chen Chen; Meng Yue Tang; Hua Dan Xue; Zheng Yu Jin; Xiao Ming Zhang (Gastroenterology Research and Practice)
Acute pancreatitis (AP) is a complex disease that results in significant morbidity and mortality. For many decades, it has compelled researchers to explore the exact pathogenesis and the understanding of the pathogenesis of AP has progressed dramatically. Currently, premature trypsinogen activation and NF-κB activation for inflammation are two remarkable hypotheses for the mechanism of AP. Meanwhile, understanding of the influence of genetic polymorphisms has resulted in tremendous development in the understanding of the advancement of complex diseases. Now, genetic polymorphisms of AP have been noted gradually and many researchers devote themselves to this emerging area. In this review, we comprehensively describe genetic polymorphisms combined with the latest hypothesis of pathogenesis associated with AP.